Ceramic glaze with eggshell glaze texture, preparation method thereof and ceramic rock plate

By using textured frit dry particles, inorganic flux and suspension agent in the glaze of ceramic rock slabs, combined with a variety of mineral components, a unique crystal structure is formed, which solves the rough texture, insufficient naturalness and gloss of ceramic rock slabs. The problem of singleness and insufficient durability achieves delicate, natural texture and high wear resistance.

CN119461852AActive Publication Date: 2025-02-18FOSHAN OCEANO CERAMICS
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411683415.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The glaze surface of the existing ceramic rock slabs has a rough texture, insufficient naturalness, single gloss, insufficient strength and hardness, and a large number of chemicals are used, which affects environmental protection and durability.

Method used

Using a combination of textured frit dry particles, inorganic flux and suspension agent, the unique crystal structure is formed to improve the glaze surface by adding mineral components such as feldspar, siliceous beryllite, garnet, silicon zinc ore and hydrochlorite. Fineness, gloss and wear resistance.

Benefits of technology

The glaze surface is as delicate and natural as an eggshell surface, which improves the comfort of the space, reduces the use of chemicals, and improves the environmental protection and durability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461852A_ABST
    Figure CN119461852A_ABST
Patent Text Reader

Abstract

The invention discloses a ceramic glaze with eggshell glaze texture, a preparation method thereof and a ceramic rock plate, the ceramic glaze is prepared from texture frit dry particles, an inorganic flux and a suspending agent, and the texture frit dry particles comprise eggshell dry particles and fluxing dry particles; the eggshell surface dry granules comprise the following raw material components in parts by weight: 11-13 parts of ice feldspar; 3-5 parts of beryllium sanite powder; and 21.5 to 24.5 parts of leucite. 5-7 parts of halloysite powder; 2.5 to 3.5 parts of diaspore powder; 5 to 7 parts of willemite; 36-40 parts of barium strontium carbonate; and 7-9 parts of magnesite. The prepared ceramic rock plate is appropriate in glossiness and transparency, the glaze surface has fine, smooth and rich-texture ceramic glaze similar to an eggshell, when the ceramic glaze is applied to the ceramic rock plate, the glossiness can be 13-15 degrees, the visible light transmittance can be 68-70, the wear resistance can reach level 5, the hardness can reach 6 or above, and the glaze surface has the fine and smooth texture of the eggshell surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building ceramics, and in particular relates to a ceramic glaze with an eggshell glaze texture, a preparation method thereof, and a ceramic rock plate. Background Art

[0002] With the continuous improvement of people's living standards, the demand for ceramic rock slabs is becoming increasingly diversified. At present, the ceramic rock slabs on the market have certain deficiencies in the glaze texture, which are mainly manifested in the following aspects: First, the glaze texture of the existing ceramic rock slabs is relatively rough, the granularity is more obvious, and it cannot reach the fineness of the eggshell surface; and the naturalness is insufficient. The existing surface treatment method is difficult to simulate the characteristics of natural organic matter. The texture and texture are relatively rigid, lacking natural randomness and variability. Second, the glossiness is single, either the bright surface is too dazzling, which is easy to cause visual fatigue; or the matte surface lacks layering and three-dimensional sense; it is impossible to achieve the comfortable texture gloss of about 15° like the eggshell surface, and the light transition is not delicate enough. Third, in order to achieve a specific glaze effect, the existing technology often adds more chemical substances, such as whitening agents, etc.; this will not only cause potential harm to human health, but also does not meet the requirements of modern society for green and environmentally friendly materials. Fourthly, the strength and hardness are not ideal. When facing external impact and wear, scratches and cracks are prone to occur, affecting the service life and appearance of the product. The corrosion resistance and stain resistance need to be improved. It cannot cope well with the erosion of various chemicals and the adhesion of stains, which brings difficulties to daily cleaning and maintenance.

[0003] In view of the shortcomings of existing ceramic rock slabs in the above-mentioned texture, gloss, environmental protection and durability, it is necessary to develop a new type of ceramic glaze to make the glaze surface have a delicate and natural texture like eggshell surface; as well as a comfortable eggshell surface texture gloss to enhance the comfort of the space; at the same time, while ensuring the glaze effect, reduce the use of chemical substances and improve the environmental performance of the product; and improve the durability of ceramic rock slabs such as strength, hardness, corrosion resistance and stain resistance, extend the service life of the product and reduce maintenance costs. Summary of the invention

[0004] The present invention proposes a ceramic glaze with an eggshell glaze texture, a preparation method thereof, and a ceramic rock plate to solve one or more technical problems existing in the prior art and at least provide a beneficial choice or create conditions.

[0005] In order to solve the above technical problems, the first aspect of the present invention provides a ceramic glaze, the preparation raw materials of which include textured frit dry particles, inorganic flux and suspending agent, the textured frit dry particles include eggshell flour dry particles and fluxing dry particles;

[0006] The raw material components of the eggshell noodle dry particles include, by weight:

[0007]

[0008]

[0009] In some embodiments of the present invention, the chemical composition of the eggshell noodle dry particles includes, by weight percentage: SiO2 35-38%; Al2O3 14-15%; Na2O 3.2-4.2%; BeO 0.5-0.8%; CaO 4-5%; MgO 4-5%; ZnO 5.5-6.2%; BaO 20.5-22%; SrO 9-10.5%.

[0010] The present invention adds various mineral components such as adularia, syenite, leucite, willemite and diaspore, and its chemical components include SiO2, Al2O3, Na2O, BeO, CaO, MgO, ZnO, BaO and SrO. These components interact with each other during the firing process to help form a unique crystal structure, thereby affecting various properties of the glaze.

[0011] Specifically, ZnO can form a wurtzite structure, which has a unique lattice arrangement, and its crystal structure has low symmetry and high anisotropy. When light enters this crystal structure, it will propagate at different speeds in different directions due to anisotropy, resulting in refraction, and the refraction angle will vary depending on the direction. This refraction property causes the light to refract and reflect multiple times inside the glaze, increasing the propagation path of the light inside the glaze, thereby making the glaze present a certain glossiness. At the same time, due to the difference in refraction in different directions, the light presents a soft and unique effect when reflected from the glaze, similar to the gloss of the eggshell surface at a specific angle. BaO reacts with other components to form a barium feldspar crystal structure, which has a relatively high refractive index. When light enters, a significant refraction phenomenon occurs. And the presence of barium feldspar crystals in the glaze changes the propagation path of light, causing the light to refract and reflect multiple times inside and on the surface of the glaze, thereby affecting the glossiness of the glaze. It works together with the crystal structure formed by other components to help achieve a glossy effect similar to the eggshell surface by adjusting the propagation and reflection of light. During the firing process, components such as CaO and MgO will form a crystal structure with higher hardness, such as calcium feldspar, magnesium aluminate spinel, etc., which is beneficial to improve the hardness and wear resistance of the glaze.

[0012] In some embodiments of the present invention, the raw material components of the inorganic flux include, by weight:

[0013]

[0014]

[0015] In some embodiments of the present invention, the chemical composition of the inorganic flux includes, by weight percentage: SiO2 47.5-57.5%; Al2O3 18-22%; Na2O 3-4%; BeO 2-3%; CaO 4-5%; MgO 4-6%; ZnO 3.5-4.5%; SrO 6.5-8.5%.

[0016] Specifically, the main chemical composition of inorganic flux is SiO2 and Al2O3, which will form a silicon-oxygen tetrahedron network structure at high temperature, which is beneficial to improve the rigidity of the glaze, enhance the structural stability, and work together with the textured frit dry particles to improve the hardness of the glaze while keeping the glaze smooth and delicate, forming a glaze effect similar to the eggshell surface. Among them: SiO2 is beneficial to increase the transparency and glossiness of the glaze, and is a glass former. During the firing process, a continuous silicon-oxygen network structure is formed, which is uniform and dense, reducing the scattering of light inside the glaze, making it easier for light to pass through the glaze, increasing transparency, reducing refraction and scattering, and making the glaze clearer and more transparent; at the same time, it makes the light reflect more regularly at the interface between the glaze and the air, improving the glossiness, similar to the bright reflection effect of a smooth glass surface. Al2O3 helps to improve the stability and hardness of the glaze and indirectly affects the glossiness. Al2O3 can form stable compounds or solid solutions with other ingredients to prevent changes or defects in the crystal structure when the glaze cools, such as combining with metal oxides to form an aluminate phase, resisting the influence of external environmental factors and maintaining the integrity and quality of the glaze; and can be filled in the glaze crystal structure to increase the bonding force between crystals, making the glaze stronger, reducing scratches and damage under the action of external forces, simulating the surface texture of eggshells, and achieving an eggshell-like surface texture.

[0017] In some embodiments of the present invention, the calcination temperature of the calcined Xuyong stone powder is 800-900° C., and the calcination time is 2-3 hours. Calcination of the Xuyong stone powder is beneficial to improving the stability and hardness of the glaze.

[0018] In some embodiments of the present invention, the particle size of the textured frit dry particles is 180-280 meshes, and the particle size deviation range is within ±8%.

[0019] In some embodiments of the present invention, the inorganic flux powder has a particle size of 200-350 meshes, and a particle size deviation range of within ±10%.

[0020] Specifically, controlling the texture frit dry particles within a finer particle size range is conducive to better fusion of particles during firing, reducing surface pores and unevenness, and improving the fineness and smoothness of the glaze. After the inorganic flux powder is mixed with the texture frit dry particles, it will fill the gaps, further improve the density and fineness and smoothness of the glaze, and improve the quality of the glaze.

[0021] In some embodiments of the present invention, the raw material components of the fluxing dry particles include, by weight:

[0022]

[0023]

[0024] In some embodiments of the present invention, the chemical composition of the fluxing dry particles includes, by weight percentage: SiO2 42-46%; Al2O3 14-16.5%; K2O 4-5%; BeO 4-6%; CaO 12-13%; MgO 3.3-4%; ZnO 1.5-1.9%; BaO 5.5-6.8%; SrO 6.5-8.5%.

[0025] Specifically, the chemical composition of the fluxing dry particles is similar to that of the eggshell surface dry particles, with only the amount of each component being different. The flux-like components in the fluxing dry particles are higher, which can change the chemical environment of the system during the firing process, better control the formation and growth of the crystal structure, and optimize the performance of the glaze. The fluxing dry particles and the eggshell surface dry particles cooperate with each other, making the crystal structure formed during the firing process more dense and uniform. This dense and uniform crystal structure not only helps to improve the mechanical properties of the glaze, but also further optimizes the optical properties of the glaze, such as gloss and transparency, to achieve a delicate, smooth and textured glaze effect similar to that of an eggshell.

[0026] In some embodiments of the present invention, the particle size of the fluxing dry particles is 200-300 meshes, and the particle size deviation range is within ±7%.

[0027] Specifically, when the fluxing dry particles are mixed with the eggshell dry particles, the two dry particles in different particle size ranges can fill the gaps between each other, further improving the density of the glaze surface, which is not only beneficial to improving the mechanical properties of the glaze surface, but also can further improve the fineness and smoothness of the glaze surface, making it closer to the texture of the eggshell surface.

[0028] In some embodiments of the present invention, the mass ratio of the textured frit dry particles to the inorganic flux is 1:(0.8-1.2).

[0029] In some embodiments of the present invention, the mass ratio of the eggshell flour dry particles to the fluxing dry particles is 1:(0.8-1.2).

[0030] In some embodiments of the present invention, the amount of the suspending agent is 1-2 wt % of the inorganic flux.

[0031] In some embodiments of the present invention, the suspending agent includes at least two of sodium polyacrylate, sodium carboxymethyl cellulose, xanthan gum, and sodium polycarboxylate.

[0032] Specifically, the combined use of multiple suspending agents is more conducive to improving the uniformity of raw material dispersion and thus improving the comprehensive performance of glazes compared to a single suspending agent. Among them: sodium polyacrylate can interact with the surface of raw material particles through the polar groups in its molecular structure, reduce the attraction between particles, and make the raw materials easier to disperse in the solvent. Sodium carboxymethyl cellulose has good water solubility and thickening properties, and can form a stable colloidal structure in the solution to prevent the precipitation of raw material particles and ensure that the raw materials are evenly distributed in the glaze slurry. Xanthan gum and sodium polycarboxylate can increase the viscosity of the solution, so that the raw material particles remain suspended in the solution, thereby improving the uniformity of raw material dispersion. The evenly dispersed raw materials are conducive to forming a denser crystal structure in the subsequent firing process, and the bonding force between crystals is stronger, thereby improving the hardness and wear resistance of the glaze. At the same time, the uniform glaze is more delicate and smooth in appearance, and is closer to the texture of eggshell surface.

[0033] The second aspect of the present invention provides a method for preparing the above-mentioned ceramic glaze, characterized in that it comprises the following steps:

[0034] (1) mixing various raw materials for preparing an inorganic flux, and performing wet ball milling to obtain an inorganic flux slurry;

[0035] (2) adding the eggshell flour dry particles and the flux dry particles into the inorganic flux slurry, adding a suspending agent, and mixing to obtain the ceramic glaze.

[0036] In some embodiments of the present invention, the viscosity of the inorganic flux slurry is 500-800 mPa·s.

[0037] The third aspect of the present invention provides a ceramic rock slab, which comprises, from bottom to top, a body layer, a surface glaze layer, a pattern layer and an eggshell surface texture glaze layer, wherein the eggshell surface texture glaze layer is formed by firing the above-mentioned ceramic glaze.

[0038] In some embodiments of the present invention, the maximum firing temperature is 1200-1220°C.

[0039] In some embodiments of the present invention, the firing cycle is 40-60 minutes.

[0040] In some embodiments of the present invention, a protective glaze layer is further included between the pattern layer and the eggshell texture glaze layer.

[0041] The present invention has no special requirements on the raw material components of the body layer, the surface glaze layer and the protective glaze layer, and the body, surface glaze and protective glaze of conventional ceramic rock panels can be used.

[0042] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:

[0043] The invention uses adularia, beryl powder, leucite, xuyong stone powder, diaspore powder, willemite, barium strontium carbonate and magnesite as raw materials to prepare eggshell flour dry particles, gives full play to the effective chemical composition of each raw material, utilizes the characteristics of each raw material and the interaction between the raw materials, and is simultaneously equipped with a certain amount of fluxing dry particles, inorganic flux and suspending agent; by optimizing and reasonably compounding each raw material, and controlling the particle size of each raw material, a ceramic glaze with suitable glossiness and transparency and a glaze surface having a delicate, smooth and textured texture similar to that of an eggshell is prepared; when the ceramic glaze is applied to a ceramic rock plate, a glossiness of 13-15°, a visible light transmittance of 68-70, a wear resistance of up to level 5, a hardness of more than 6, and a glaze surface having a delicate and smooth texture of an eggshell surface can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is a physical picture of the glaze surface of the ceramic rock plate prepared in Example 1;

[0045] Figure 2 This is a physical picture of the glaze surface of the ceramic rock plate prepared in Comparative Example 1;

[0046] Figure 3 This is a physical picture of the glaze surface of the ceramic rock plate prepared in Comparative Example 3;

[0047] Figure 4 This is a physical picture of the glaze surface of the ceramic rock plate prepared in Comparative Example 4;

[0048] Figure 5 This is a real picture of the glaze of the ceramic rock slab prepared in Comparative Example 6. DETAILED DESCRIPTION

[0049] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.

[0050] The raw material components of the green body used in the examples and comparative examples of the present invention include, by weight: 35 parts of kaolin, 30 parts of feldspar, 20 parts of quartz, 15 parts of clay, and 5 parts of talc.

[0051] The raw material components of the surface glaze layer include, by weight: 40 parts of potassium feldspar, 20 parts of calcite, 15 parts of dolomite, 5 parts of zinc oxide, 15 parts of quartz, 8 parts of calcined talc, and 1 part of sodium carboxymethyl cellulose (CMC).

[0052] Example 1

[0053] A ceramic glaze, wherein the raw materials for preparing the glaze include, by weight, 100 parts of textured frit dry particles, 100 parts of inorganic flux and 1.5 parts of suspending agent, wherein the textured frit dry particles include eggshell flour dry particles and fluxing dry particles in a mass ratio of 1:1.

[0054] Among them: the raw material components of the eggshell flour granules include, by weight:

[0055]

[0056] The chemical composition of the eggshell flour particles includes, by weight percentage: SiO2 36%, Al2O3 14.5%, Na2O3 3.7%, BeO 0.65%, CaO 4.5%, MgO 4.5%, ZnO 5.8%, BaO 20.6%, and SrO 9.75%.

[0057] The raw material components of the inorganic flux include, by weight:

[0058]

[0059]

[0060] The chemical composition of the inorganic flux, by weight percentage, includes: SiO2 62.5%; Al2O3 24%; Na2O3.5%; BeO2.5%; CaO 4.5%; MgO 5%; ZnO 4%; SrO 7.5%.

[0061] The raw material components of the fluxing dry particles include, by weight:

[0062]

[0063] The chemical composition of the fluxing dry particles, by weight percentage, includes: SiO2 44%; Al2O3 15%; K2O 4.5%; BeO 5%; CaO 12.5%; MgO 3.65%; ZnO 1.7%; BaO 6%; SrO 6.85%.

[0064] The suspending agent comprises sodium carboxymethyl cellulose, xanthan gum and sodium polycarboxylate in a mass ratio of 3:3:4.

[0065] The method for preparing the ceramic glaze comprises the following steps:

[0066] (1) According to the raw material ratio, various raw materials for preparing the inorganic flux are weighed, and deionized water is added for wet ball milling (the mass ratio of the material to the water is 1:1.75) and sodium polyacrylate (the amount added is 1.5% of the total mass of the inorganic flux), and stirred at a speed of 900 rpm for 1.5 hours to obtain an inorganic flux slurry with a viscosity of 650 mPa·s, a particle size of 200 mesh, and a particle size deviation range of within ±10%;

[0067] (2) weighing the raw materials for preparing the eggshell flour dry particles according to the raw material ratio, melting them and pouring them into water for quenching to obtain fused particles; then crushing the fused particles to obtain eggshell flour dry particles with a particle size of 180 mesh and a particle size deviation range of less than ±8%;

[0068] (3) weighing the raw materials for preparing the flux dry particles according to the raw material ratio, pouring them into water for quenching after melting, and obtaining frit particles; then crushing the frit particles to obtain flux dry particles with a particle size of 250 mesh and a particle size deviation range of within ±7%;

[0069] (4) Add the eggshell flour dry particles and flux dry particles into the inorganic flux slurry, add a suspending agent, and mix well to obtain the ceramic glaze of this embodiment.

[0070] A method for preparing a ceramic rock plate comprises the following steps:

[0071] The surface glaze, inkjet-printed pattern and the above-mentioned ceramic glaze are sequentially poured on the blank to form a surface glaze layer, a pattern layer and an eggshell-textured glaze layer in sequence. After drying, the blank is put into a kiln and fired at 1220°C for 60 minutes to obtain the ceramic rock slab of this embodiment.

[0072] Example 2

[0073] A ceramic glaze, wherein the raw materials for preparing the glaze include, by weight, 100 parts of textured frit dry particles, 90 parts of inorganic flux and 1.35 parts of suspending agent, wherein the textured frit dry particles include eggshell flour dry particles and fluxing dry particles in a mass ratio of 1:1.2.

[0074] Among them: the raw material components of the eggshell flour granules include, by weight:

[0075]

[0076] The chemical composition of the eggshell flour particles includes, by weight percentage: SiO2 35.5%; Al2O3 14.5%; Na2O3.7%; BeO 0.65%; CaO 4.5%; MgO 4.5%; ZnO 5.85%; BaO 21.25%; SrO 9.55%.

[0077] The raw material components of the inorganic flux include, by weight:

[0078]

[0079] The chemical composition of the inorganic flux, by weight percentage, includes: SiO2 52.5%; Al2O3 20.5%; Na2O3.5%; BeO 2.5%; CaO 4.5%; MgO 5%; ZnO 4%; SrO 7.5%.

[0080] The raw material components of the fluxing dry particles include, by weight:

[0081]

[0082]

[0083] The chemical composition of the fluxing dry particles, by weight percentage, includes: SiO2 44%; Al2O3 15%; K2O 4.5%; BeO 5%; CaO 12.5%; MgO 3.65%; ZnO 1.7%; BaO 6%; SrO 7.65%.

[0084] The suspending agent comprises sodium carboxymethyl cellulose, xanthan gum and sodium polycarboxylate in a mass ratio of 3:3:4.

[0085] The method for preparing the ceramic glaze comprises the following steps:

[0086] (1) According to the raw material ratio, various raw materials for preparing the inorganic flux are weighed, and deionized water is added for wet ball milling (the mass ratio of the material to the water is 1:1.75) and sodium polyacrylate (the amount added is 1.5% of the total mass of the inorganic flux), and stirred at a speed of 900 rpm for 1.5 hours to obtain an inorganic flux slurry with a viscosity of 650 mPa·s, a particle size of 350 mesh, and a particle size deviation range of within ±10%;

[0087] (2) weighing the raw materials for preparing the eggshell flour dry particles according to the raw material ratio, melting them and pouring them into water for quenching to obtain fused particles; then crushing the fused particles to obtain eggshell flour dry particles with a particle size of 280 mesh and a particle size deviation range of less than ±8%;

[0088] (3) weighing the raw materials for preparing the flux dry particles according to the raw material ratio, pouring them into water for quenching after melting, and obtaining frit particles; then crushing the frit particles to obtain flux dry particles with a particle size of 300 mesh and a particle size deviation range of within ±7%;

[0089] (4) Add the eggshell flour dry particles and flux dry particles into the inorganic flux slurry, add a suspending agent, and mix well to obtain the ceramic glaze of this embodiment.

[0090] A method for preparing a ceramic rock plate comprises the following steps:

[0091] The surface glaze, inkjet-printed pattern and the above-mentioned ceramic glaze are sequentially poured on the blank to form a surface glaze layer, a pattern layer and an eggshell-textured glaze layer in sequence. After drying, the blank is put into a kiln and fired at 1220°C for 60 minutes to obtain the ceramic rock slab of this embodiment.

[0092] Example 3

[0093] A ceramic glaze, wherein the raw materials for preparing the glaze include, by weight, 100 parts of textured frit dry particles, 100 parts of inorganic flux and 1.5 parts of suspending agent, wherein the textured frit dry particles include eggshell flour dry particles and fluxing dry particles in a mass ratio of 1:1.

[0094] Among them: the raw material components of the eggshell flour granules include, by weight:

[0095]

[0096]

[0097] The chemical composition of the eggshell flour particles includes, by weight percentage: SiO2 36%, Al2O3 14.5%, Na2O3 3.7%, BeO 0.65%, CaO 4.5%, MgO 4.5%, ZnO 5.8%, BaO 20.6%, and SrO 9.75%.

[0098] The raw material components of the inorganic flux include, by weight:

[0099]

[0100] The chemical composition of the inorganic flux, by weight percentage, includes: SiO2 52.5%; Al2O3 20%; Na2O 4%; BeO 2.5%; CaO 4.5%; MgO 5%; ZnO 4%; SrO 7.5%.

[0101] The raw material components of the fluxing dry particles include, by weight:

[0102]

[0103] The chemical composition of the fluxing dry particles, by weight percentage, includes: SiO2 44%; Al2O3 15%; K2O 4.5%; BeO 5%; CaO 12.5%; MgO 3.65%; ZnO 1.7%; BaO 6%; SrO 7.65%.

[0104] The suspending agent comprises sodium carboxymethyl cellulose, xanthan gum and sodium polycarboxylate in a mass ratio of 3:3:4.

[0105] The method for preparing the ceramic glaze comprises the following steps:

[0106] (1) According to the raw material ratio, various raw materials for preparing the inorganic flux are weighed, and deionized water is added for wet ball milling (the mass ratio of the material to the water is 1:1.75) and sodium polyacrylate (the amount added is 1.5% of the total mass of the inorganic flux), and stirred at a speed of 900 rpm for 1.5 hours to obtain an inorganic flux slurry with a viscosity of 650 mPa·s, a particle size of 300 mesh, and a particle size deviation range of within ±10%;

[0107] (2) weighing the raw materials for preparing the eggshell flour dry particles according to the raw material ratio, melting them and pouring them into water for quenching to obtain fused particles; then crushing the fused particles to obtain eggshell flour dry particles with a particle size of 260 mesh and a particle size deviation range of less than ±8%;

[0108] (3) weighing the raw materials for preparing the flux dry particles according to the raw material ratio, pouring them into water for quenching after melting, and obtaining frit particles; then crushing the frit particles to obtain flux dry particles with a particle size of 250 mesh and a particle size deviation range of within ±7%;

[0109] (4) Add the eggshell flour dry particles and flux dry particles into the inorganic flux slurry, add a suspending agent, and mix well to obtain the ceramic glaze of this embodiment.

[0110] A method for preparing a ceramic rock plate comprises the following steps:

[0111] The surface glaze, inkjet-printed pattern and the above-mentioned ceramic glaze are sequentially poured on the blank to form a surface glaze layer, a pattern layer and an eggshell-textured glaze layer in sequence. After drying, the blank is put into a kiln and fired at 1220°C for 60 minutes to obtain the ceramic rock slab of this embodiment.

[0112] Comparative Example 1

[0113] The difference between Comparative Example 1 and Example 1 is that an equal amount of potassium feldspar is used to replace adularia in the raw material component of the eggshell flour dry particles in the ceramic glaze of Comparative Example 1.

[0114] Comparative Example 2

[0115] The only difference between Comparative Example 2 and Example 1 is that no silicate stone powder is added to the raw material components of the eggshell flour dry particles in the ceramic glaze of Comparative Example 2.

[0116] Comparative Example 3

[0117] The only difference between Comparative Example 3 and Example 1 is that no diaspore powder is added to the raw material components of the eggshell flour dry particles in the ceramic glaze of Comparative Example 3.

[0118] Comparative Example 4

[0119] The only difference between Comparative Example 4 and Example 1 is that the ceramic glaze of Comparative Example 4 does not contain an inorganic flux.

[0120] Comparative Example 5

[0121] The only difference between Comparative Example 5 and Example 1 is that the particle sizes of the texture frit dry particles and the inorganic flux in the ceramic glaze of Comparative Example 5 are the same, both of which are 180-280 meshes, and the particle size deviation range is within ±8%.

[0122] Comparative Example 6

[0123] The only difference between Comparative Example 6 and Example 1 is that the suspending agent in the ceramic glaze of Comparative Example 6 is a single sodium carboxymethyl cellulose.

[0124] Performance Testing

[0125] The ceramic rock plate samples prepared in the above Examples 1-3 and Comparative Examples 1-6 were tested for Mohs hardness, wear resistance, glossiness, and light transmittance performance of the eggshell texture glaze layer. Among them: the wear resistance is tested according to GB / T3810.7-2016 "Determination of surface wear resistance of ceramic glazed tiles"; the light transmittance is tested according to GB2680-2021 "Determination of visible light transmittance, direct sunlight transmittance, total solar energy transmittance, ultraviolet transmittance and related window glass parameters of architectural glass". The test results are shown in Table 1.

[0126] Table 1:

[0127]

[0128] As shown in Table 1, the glossiness of the ceramic rock slabs prepared in Examples 1-3 is 13-15°, which is similar to the glossiness of the eggshell surface texture; the glaze surface has a high hardness of more than 6, and the wear resistance level can reach the highest level 5; the glaze surface has good light transmittance, and the visible light transmittance ratio reaches 68-70%; and the glaze surface has the delicate and smooth texture of the eggshell surface, such as Figure 1 shown.

[0129] Comparative Examples 1-3 Compared with Example 1, since potassium feldspar is used in place of adularia in the raw material components of the eggshell flour dry particles in the ceramic glaze, and beryllium silicate powder and diaspore powder are not added, the glossiness and light transmittance of the glaze surface are reduced to a certain extent, resulting in a decrease in the texture and fineness of the glaze surface. Figure 2 ; There are even glaze defects such as cracks, see Figure 3 ; At the same time, hardness and wear resistance also decrease.

[0130] Comparative Example 4 Compared with Example 1, since the ceramic glaze does not contain inorganic flux, a good silicon-oxygen tetrahedral network structure cannot be formed, the density of the glaze surface decreases, and the light scattering is serious, resulting in a significant decrease in the hardness and wear resistance of the glaze surface, as well as the glossiness and light transmittance, resulting in a dull glaze surface and the presence of concave glaze phenomenon, see Figure 4 .

[0131] Compared with Example 1, since the particle sizes of the textured frit dry particles and the inorganic flux in the ceramic glaze are the same, the growth and distribution of crystals in the glaze layer are affected, resulting in a decrease in the hardness and wear resistance of the glaze surface, and the glaze surface uniformity is poor.

[0132] Comparative Example 6 Compared with Example 1, the suspending agent in the ceramic glaze is a single sodium carboxymethyl cellulose, which leads to a decrease in the dispersion and suspension of the glaze slurry, resulting in a slight decrease in the hardness, wear resistance and light transmittance of the glaze surface, and the glaze surface uniformity is not good. Figure 5 .

[0133] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.

Claims

1. A ceramic glaze, characterized in that: The preparation raw materials include textured frit dry particles, inorganic flux and suspending agent, wherein the textured frit dry particles include eggshell flour dry particles and fluxing dry particles; The raw material components of the eggshell noodle dry particles include, by weight:

2. The ceramic glaze according to claim 1, characterized in that: The raw material components of the inorganic flux include, by weight:

3. The ceramic glaze according to claim 1 or 2, characterized in that: The particle size of the textured frit dry particles is 180-280 meshes, and the particle size deviation range is within ±8%; and / or the particle size of the inorganic flux powder is 200-350 meshes, and the particle size deviation range is within ±10%.

4. The ceramic glaze according to claim 1, characterized in that: The raw material components of the fluxing dry particles include, by weight:

5. The ceramic glaze according to claim 1 or 4, characterized in that: The particle size of the fluxing dry particles is 200-300 meshes, and the particle size deviation range is within ±7%.

6. The ceramic glaze according to claim 1, characterized in that: The mass ratio of the textured frit dry particles to the inorganic flux is 1:(0.8-1.2); and / or, the mass ratio of the eggshell flour dry particles to the fluxing dry particles is 1:(0.8-1.2); and / or, the amount of the suspending agent is 1-2wt% of the inorganic flux.

7. The ceramic glaze according to claim 1, characterized in that: The suspending agent includes at least two of sodium polyacrylate, sodium carboxymethyl cellulose, xanthan gum, and sodium polycarboxylate.

8. A method for preparing a ceramic glaze according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) mixing various raw materials for preparing an inorganic flux, and performing wet ball milling to obtain an inorganic flux slurry; (2) adding the eggshell flour dry particles and the flux dry particles into the inorganic flux slurry, adding a suspending agent, and mixing to obtain the ceramic glaze.

9. A ceramic rock plate, characterized in that: It comprises a body layer, a surface glaze layer, a pattern layer and an eggshell surface texture glaze layer from bottom to top, and the eggshell surface texture glaze layer is fired by the ceramic glaze according to any one of claims 1-7.

10. The ceramic rock plate according to claim 9, characterized in that: The maximum firing temperature is 1200-1220° C.; and / or the firing period is 40-60 min.

Citation Information

Patent Citations

  • Double-crystal-flower colored crystal glaze, double-crystal-flower colored crystal glaze ceramic tile and preparation method of double-crystal-flower colored crystal glaze ceramic tile

    CN115959828A

  • Fine and smooth glaze, fine and smooth skin type ceramic rock plate and preparation method of fine and smooth glaze and fine and smooth skin type ceramic rock plate

    CN118164675A

  • Wear-resistant matte ceramic rock plate and preparation method thereof

    CN118479733A

  • Eggshell glaze, high-whiteness glazed tile and preparation method thereof

    CN118495812A